2021
DOI: 10.3390/e23050567
|View full text |Cite
|
Sign up to set email alerts
|

Computational Modeling of Boundary Layer Flashback in a Swirling Stratified Flame Using a LES-Based Non-Adiabatic Tabulated Chemistry Approach

Abstract: When operating under lean fuel–air conditions, flame flashback is an operational safety issue in stationary gas turbines. In particular, with the increased use of hydrogen, the propagation of the flame through the boundary layers into the mixing section becomes feasible. Typically, these mixing regions are not designed to hold a high-temperature flame and can lead to catastrophic failure of the gas turbine. Flame flashback along the boundary layers is a competition between chemical reactions in a turbulent flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…On the other hand, it has been reported that the flamelet-generated manifold (FGM) approach can simulate the partially premixed combustion with the relatively low calculation cost and the satisfactory accuracy [18][19]. In addition, the heat loss process, which is important for boundary layer flashback, could be taken into account in the FGM approach [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been reported that the flamelet-generated manifold (FGM) approach can simulate the partially premixed combustion with the relatively low calculation cost and the satisfactory accuracy [18][19]. In addition, the heat loss process, which is important for boundary layer flashback, could be taken into account in the FGM approach [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The drive towards carbon neutrality has recently prompted a growth in demand for clean and renewable fuels. Such a development promoted an intensification of research into the utilization of hydrogen-enriched fuels, which is accompanied with challenges such as flame flashback, an event potentially destructive for a combustion chamber [1][2][3][4][5]. The flame flashback phenomenon can be briefly described as flame propagation against the stream of gas in a fuel passage, and it can be conventionally classified [1,6] Recently, activity in experimental and numerical studies of BLF has been increasing, covering both studies of flashback fundamentals and engineering applications [7][8][9].…”
Section: Introductionmentioning
confidence: 99%